Analysis of Income Tax Article 21 Implementation on Overseas Living Allowance of Government Officials: A Case Study of Indonesian Trade Promotion Centre Work Units - Raka Adityo Kurniawan; Tony Sudirgo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study analyzes the effect of Non-Taxable Income (PTKP), Civil Servant Grade, and the Overseas Living Allowance (TPLN) in the accreditation country on the amount of Income Tax Article 21 (PPh Article 21) withheld from the salaries of State Civil Apparatus (ASN) assigned to Indonesian Trade Promotion Centre (ITPC) work units. A quantitative approach with a causal-comparative research design was employed. Secondary data were collected from personnel and tax administrative records of 38 ASN — comprising the Head and Deputy Head of ITPC — from 19 work units located across various countries. Multiple linear regression analysis was conducted using SPSS version 25. Results indicate that simultaneously, PTKP, Civil Servant Grade, and Country TPLN significantly influence PPh Article 21 (F = 4,971.913; Sig. = 0.000; Adjusted R² = 0.998). Partially, only Country TPLN shows a positive and highly significant effect (t = 109.349; Sig. = 0.000; β = 1.005), while PTKP (Sig. = 0.746) and Civil Servant Grade (Sig. = 0.070) are not significant individually. The application of the Average Effective Rate (TER) method under Government Regulation No. 58 of 2023 demonstrates a highly accurate withholding model. These findings contribute to the literature on overseas civil servant taxation and provide actionable policy recommendations for the Ministry of Trade and Ministry of Finance.